(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Of late, incidence of gunshot injuries are exhibiting a quantum leap owing to easy availability of firearms. Abdominal gunshot ranged from minor superficial pellet injuries to devastating soft tissues and visceral injuries. The study included 30 cases of abdominal gunshot and other associated injuries admitted to surgery wards of SRN Hospital. Younger age group (21-30 yrs) was more commonly involved 7(23.33%). M: F ratio was 6.5:1. The rural-urban ratio was 1.5:1. Most cases 20(66.67%) were due to assault. 24(80%) received bullet injuries and 6(20%) shotgun injuries. In 19(63.33%) cases 0.315 mm bullet was responsible, of these 15(50%) were due to country made ‘Katta’. 0.32 mm bullet was used only in 4(13.33%) cases. 28 were operated upon and in 2 cases of pellet injury (Type-I) conservative management was done. 22 patients of bullet and 5 pellet injuries were recovered and 3 cases expired.